1996
DOI: 10.1111/j.1365-2990.1996.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in the olfactory system of dogs

Abstract: Age-related changes in the olfactory system were examined in 22 dogs ranging in age from 10 to 19 years old. Atrophic changes with degeneration were observed in the olfactory epithelium of dogs older than 14 years; the changes were prominent in the dogs over the age of 17 years. Immunohistochemistry using an anti-carnosine antibody, which is a marker for the olfactory cells, demonstrated a decrease in the number of olfactory cells. Electron microscopy also showed a decrease in the number of cilia of olfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…Aging studies have shown a decrease in both the number and the length of epithelial microvilli and a declined function of plasma membrane enzymes and receptors (32)(33)(34)(35). Specifically, the decrease in the activity of some of the enzymes …”
Section: Discussionmentioning
confidence: 99%
“…Aging studies have shown a decrease in both the number and the length of epithelial microvilli and a declined function of plasma membrane enzymes and receptors (32)(33)(34)(35). Specifically, the decrease in the activity of some of the enzymes …”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes including neuronal loss [23], gliosis [22] and deposition of ubiquitin-positive granules [9,16] have been demonstrated in the brain of dog. Liu et al [15] reported the age-related decrease of synaptic density in the cerebral cortex of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting neurogenesis occurs in humans as well; when OE was isolated from middle aged and elderly postmortem OE and grown in vitro , some newborn cells did express OMP, albeit at a low rate (Hahn et al, 2005). However, as in the VNO, the rate of proliferation in the OE also declines with age [mouse (Loo et al, 1996); guinea pig (Nakamura et al, 1998); and dog (Hirai et al, 1996)]. Similar to the VNO, during the first year of life in the rat OE, neurogenesis was shown to contribute largely to growth rather than replacement (Weiler and Farbman, 1997).…”
Section: The Effect Of Organismal Age On Neurogenesis In the Olfactormentioning
confidence: 99%